Earth, water, and fire the prehistoric pottery of Mesa Verde - Oppelt, Norman T. (Johnson Books Boulder, Colorado, 1991)
A discussion, aimed at the general reader, of the prehistoric pottery from the Mesa Verde National Park. Mesa Verde prehistoric remains constitute one division of what Southwestern archaeologists recognize as the Anasazi Culture or tradition in the region. The book is well illustrated, with maps and charts and a large number of photographs of Mesa Verde pottery styles, many in color. Oppelt discusses the development over time of Mesa Verde pottery, explains how Anasazi pottery was made, and explores how pottery was used by the prehistoric people at Mesa Verde
66664
Keywords: Pueblo Indians -- Pottery; Pueblo Indians -- Antiquities; Mesa Verde National Park (Colo)